The Influence of Service Quality, Customer Value, and Corporate Image on Customer Loyalty (Case Study of PT BNI Syariah Tanah Abang Branch) - Anggraini, Zulfa; Rizal, Sofyan (Budapest International Research and Critics University, 2025)
The purpose of study was to analyze the effect of service quality., customer value and company image on customer loyalty at PT. BNI Syariah Tanah Abang Branch. The type of research is quantitative. The data source of study is primary data derived from the sample, namely the customers of PT. BNI Syariah Tanah Abang Branch. Data collection was done using purposive sampling by spreading to 100 respondents. This study uses multiple linier regression analysis method. The results of study show that 1) service quality doesn’t significantly influence customer loyalty. 2) customer value significantly influences customer loyalty. 3) company image significantly influence customer loyalty, and 4) service quality, customer value and influential company image significantly influence customer loyalty.